SEMI-ARID LANDSCAPES AND DESERTIFICATION: GEOBIOPHYSICAL INDICATORS OF RELIEF, CLIMATE AND WATER RESOURCES IN THE HYDROGRAPHIC SUB-BASIN OF RIO FIGUEIREDO, CEARÁ - Souza, Anny Catarina Nobre de; Souza, Sérgio Domiciano Gomes de; Sousa, Maria Losângela Martins de (Geosaberes; Vol 13 (2022), 2022)
Since Desertification, par excellence, is a serious environmental problem of drylands, this study aims to analyze the susceptibility to Desertification in the Figueiredo River sub-basin, Ceará state, from the geobiophysical indicators of climate, relief and water resources. For this purpose, the geosystemic analysis in hydrographic basins and the geobiophysical indicators of Desertification by Abraham and Beekman (2006) adapted by Oliveira (2012) were adopted as a theoretical-methodological basis. As for the procedures adopted, a literature review, collection and analysis of secondary data, surveys and elaboration of cartographic products and fieldwork were carried out. The behavior of each indicator was investigated, together in the environmental systems of the sub-basin, indicating variations in susceptibility from low and from moderate to very high.